Pelatihan Kelompok Guru dalam Penerapan Strategi Joyful Learning di Madrasah Ibtidaiyah - Rohmah, Annisa Nidaur; Nisa', Rofiatun; Mufaizin, Mufaizin (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Community service activities aim to provide solutions to teachers in dealing with students who lack interest and enthusiasm in the learning process, provide material to teachers regarding the application of joyful learning in the learning process and assist Madrasas in improving the quality of human resources which previously experienced obstacles by several factors such as the difficulty of carrying out training due to internal funding, limited creative learning training activities for teachers at Madrsah Ibtidaiyah. In this service, the Asset Bassed Community-Driven Development (ABCD) approach is used with preparation, implementation and reporting methods. Based on the results of implementing Community Service activities at MI Aisyatul Wahidah, it can be concluded that this training can provide increased understanding of Joyful Learning, increase Teacher Ability in Designing Joyful Learning and improve the Quality of Learning by Teachers in each Class by implementing the Joyful Learning integrated with media, methods and learning models according to the material to be presented in class.